Middle Range Theory of Traumatic Childbirth - Cheryl Tatano Beck (SAGE Publishing, 2015)
A middle range theory of traumatic childbirth was developed using Morse's method of theoretical coalescence. The scope of this qualitative theory was increased by formalizing the connections between 14 individual studies all conducted by the same researcher on the same topic, with different groups, using different research designs and different types of analyses. Axioms were derived from this research program along with attributes of traumatic childbirth, posttraumatic stress, and secondary traumatic stress. This middle range theory addresses the long-term chronic consequences of a traumatic birth for mothers including its impact on breastfeeding, subsequent childbirth, and the anniversary of birth trauma. The impact on fathers and clinicians present at the traumatic birth is highlighted as secondary traumatic stress comes into play. Troubling glimpses of difficulties in mother-infant bonding are revealed.